Attitude of farmers towards grape cultivation and export - RAMESH, NIKAM VINAYAK; SINGH, PREMLATA; CHAHAL, V P (The Indian Journal of Agricultural Sciences, 2015)
Adoption behavior of farmers is affected by the attitude they possess for particular technology. Many grape growers became successful exporters by associating themselves to Mahagrapes, necessitating need to study their attitude scientifically and empirically. Study of 90 grape growers who were members of cooperatives linked to Mahagrapes, from Nashik, Sangli and Pune districts of Maharashtra found that members had long association with Mahagrapes with average of 15 years. They earned average Rupees 13.3 lakh per annum by exporting their produce. Average land holding was 10 acres and productivity of grapes obtained was 11.7 tonnes/acre. Farmers had more favourable attitude towards grapes cultivation as result of their association with Mahagrapes. Total annual income, risk taking behavior and achievement motivation of members were positively and significantly related to attitude towards grape cultivation and export. Thus, study implied that farmer’s organization like Mahagrapes helped in developing positive attitude among farmers towards grape cultivation and export, motivating them to earn more income annually by exporting their produce.